The Relationship Between Adolescent Knowledge About HIV/AIDS and Stigma Toward PLWHA at the Faculty of Health Sciences - Simon, Maria Getrida; Hepilita, Yohana; Mariati, Lusia Henny (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
HIV/AIDS is one of the Millennium Development Goals (MDGs) in the health sector, alongside efforts to combat Malaria and Tuberculosis (TB), with a focus on controlling the spread of new cases. One of the measures to control transmission is ensuring that people living with HIV (PLWHA) adhere to antiretroviral (ARV) treatment. Stigma refers to a negative attribute attached to an individual due to environmental influences. This stigma often leads to discrimination, which is defined as unjust treatment of individuals based on their actual or perceived HIV status or overall health condition. This study is a quantitative research using a descriptive correlational design with a cross-sectional approach. Data collection was conducted through questionnaires distributed via Google Form. The sample consisted of all first-year students of the Nursing Study Program, Faculty of Health Sciences, Catholic University od Santu Paulus Ruteng, totaling 129 participants. The sampling technique used was purposive sampling, with the inclusion criteria being: willingness to participate and being a first-year student preparing for clinical practice. A chi-square statistical test resulted in a p-value of 0.025, indicating a significant relationship between adolescent knowledge and stigma toward PLWHA. As future nurses, it is essential for nursing students to enhance their knowledge to avoid harboring negative stigma when providing care for PLWHA.